Displacement decomposition and parallelisation of the PCG method for elasticity problems. (8th May 2006) - Blaheta, Radim; Jakl, Ondrej; Stary, Jiri
This paper describes the displacement decomposition for elasticity problems solved by the finite element method. This decomposition can be used for parallel implementation of the conjugate gradient solvers and construction of parallelisable preconditioners. Both the fixed and variable preconditioning can be applied according to the solution of subproblems. Numerical efficiency of the parallel algorithms is demonstrated on an academic benchmark and real-life modelling problem. A comparison with a domain decomposition technique is also provided.